Semillas en disputa: Historias de vida y memorias del cambio tecnológico en la agricultura de la papa en Costa Rica (1943-2015) - Coto Cedeño, Wainer Ignacio (2015)
This paper analyzes the process of technological change in agriculture potato in Costa Rica between 1943 and the present. Research shows that the adoption of technological change was an uneven process, which favored the economically better off farmers and displaced others with fewer resources to access modern inputs. This led to the emergence of frictions and conflicts between small, medium and large farmers. The study reviewed literature documentation, the National Archives, as well as annual reports of the Ministry of Agriculture, in addition to press articles. Also it uses oral history and includes interviews with producers and agronomists of the Ministerio de Agricultura y Ganadería (MAG) and the private sector.